Social Mobility of Russians in Terms of Life Chances and Risks - SlobodenyukEkaterina D. (Journal of Economic Sociology, 2022)
This paper focuses on the issues of social mobility and immobility of Russians in the neo-Weberian stratification hierarchy of Russian society, based on indicators of life chances. Social mobility is interpreted as a transition between three mass strata. Trajectories of mobility (rates and factors) are analyzed using the Russian Longitudinal Monitoring Survey (RLMS) panel data of a six-year interval from 2013 to 2018 and the group-based trajectory modeling (GBTM) method. It is shown that a quarter of Russians moved between strata. Mobility usually occurs over a short distance. Cases of significant life changes that would lead to transition between polar strata (low and high) are exceptions to the rule. The chances of getting into polar strata depend on the quality of human potential and, as a result, on individuals’ places in the system of industrial relations. Only highly qualified Russians with good health, who also originate from highly educated families, have high chances of getting into positively privileged (high) strata. For these Russians, composite rents work. Risks of moving down to low strata are present for Russians with low education, bad health and parents with low education, mainly due to employment in bad job positions that violate employees’ rights. The paper shows that social background continues to play a significant role in shaping chances of social wellbeing and mobility. It also draws attention to the fact that skills in use of information technology form a new basis for inequality between people.